Instances of animal traction in the Neolithic village of Chalain (Jura, France). End of the 31st century BC - Arbogast, Rose-Marie; Pétrequin, Pierre; Pétrequin, Anne-Marie; Maréchal, Denis; Viellet, Amandine (Archaeofauna, 2003)
Resumen